Impact of derivative products on monetary policy objectives: A general equilibrium model - Bernal Ponce, L. Arturo; Venegas Martínez, Francisco (Estudios Económicos de El Colegio de México, 2011)
This paper is aimed in analyzing the impact of the growing use of contingent claims in the objectives of monetary policy. To reach this end, a continuous time, stochastic model of macroeconomic equilibrium of a monetary economy where the agents are exposed to the risk market is developed. In the equilibrium the inflation rate is endogenously determined as a function of the trend and volatility of risky assets such as derivatives. The main results are: 1) the growing use of derivatives has a significant effect on the rate of inflation, and 2) under certain conditions, an increase in the volatility of the derivatives market has a negative effect on inflation.